Methyl orange dye sequestration using polyaniline nanotube-filled sodium alginate bio-composite microbeads - Yildirim, Sevval; Isik, Birol; Ugraskan, Volkan (ELSEVIER SCIENCE SA, 2023)
Dye pollution is a significant problem in today's environmental protection, and bio-adsorbents have been getting a lot of attention in wastewater treatment because of their affordability, sustainability, and eco-friendly. Biobased sodium alginate-polyaniline nanotube (SA-PANINT) composite microbeads were fabricated by a facile cross-linking with calcium chloride solution for the adsorptive removal of methyl orange (MO) dye. Depending on the amount of PANINT in the composite composition, SA-PANINT-10, SA-PANINT-20, SA-PANINT-30, and SA-PANINT-40 composite microbeads were prepared. Among these microbeads, SA-PANINT-30 composite microbeads gave the best results in experimental tests. The obtained SA-PANINT-30 composite microbeads were characterized by FTIR-ATR, SEM, XRD, and BET analyses, and the influence of dose (0.01 g/50 mL-0.15 g/50 mL), pH (2-12), time (0-210 min), and concentration (10-50 mg/L) on the adsorption of MO was examined. From the Langmuir isotherm model, under optimum conditions, the qm value of SA-PANINT-30 microbeads was determined as 370.4 mg/g at 25 degrees C. It was also obtained that the adsorption process followed the PSO model and the adsorption process took place chemically. From the thermodynamic parameters, the adsorption process for SA-PANINT-30 microbeads was found to be endothermic (& UDelta;Ho = 24.09 kJ/mol) and spontaneous (& UDelta;Go = -25.56 kJ/mol at 25 degrees C). Considering all these results, it was seen that the prepared composite microbeads can be used as a highly efficient, low-cost, sustainable, and potential adsorbent in the removal of synthetic anionic dyes from wastewater.
Keywords: Adsorption; Composite microbeads; PANI nanotubes; Sodium alginate; Methyl orange; EFFICIENT ADSORPTION; PHOTOCATALYTIC ACTIVITY; CONDUCTING POLYMER; AQUEOUS-SOLUTIONS; CHARGE-TRANSPORT; HIGHLY EFFICIENT; ANIONIC DYES; REMOVAL; BLUE; ADSORBENT; Materials Science